Sampled-data modeling and analysis of one-cycle control and charge control. - Chung-Chieh Fang (IEEE Transactions on power electronics)
Sampled-data modeling and analysis are applied to PWM DC-DC converters under one-cycle control or its special case, charge control. These two control schemes are analyzed in a unified framework. Large-signal analysis, steady-state analysis and small-signal analysis are addressed analytically. The orbital nature of the nominal periodic solution is preserved. Various transfer functions are derived. Compared with the averaging approach, the sampled-data approach is more accurate and systematic